Pengaruh Pertumbuhan Ekonomi, Pendidikan, dan Kesehatan Terhadap Pembangunan Manusia di Indonesia tahun 2016-2023 - Sari, Riska Cempaka; Widyawati, Retno Febriyastuti (Economie: Jurnal Ilmu Ekonomi, 2025)
One of the criteria used to see the quality of human life is the Human Development Index (HDI), which is measured by the quality of education, health, and economy (earning power). This study aims to determine how the influence of economic growth, education, health on human development in Indonesia. The purpose of this study is to determine the effect of economic growth, education, health on human development in Indonesia for the period 2016-2023. The method used in this research is panel data regression analysis. Panel data is combined data between cross section data (across places) and time series (time series). The results of this study concluded that economic growth, education and health have a positive and significant effect partially and simultaneously on the Human Development Index. GRDP variables, average years of schooling, life expectancy partially and simultaneously affect the human development index in Indonesia.